Rapid Effects of Vagus Nerve Stimulation on Sensory Processing Through Activation of Neuromodulatory Systems - Rodenkirch, Charles; Carmel, Jason B.; Wang, Qi (Frontiers in Neuroscience, 2022)
After sensory information is encoded into neural signals at the periphery, it is processed through multiple brain regions before perception occurs (i.e., sensory processing). Recent work has begun to tease apart how neuromodulatory systems influence sensory processing. Vagus nerve stimulation (VNS) is well-known as an effective and safe method of activating neuromodulatory systems. Supporting this hypothesis, there is a growing body of studies confirming VNS has immediate effects on sensory processing across multiple sensory modalities. These immediate effects of VNS on sensory processing are distinct from the more well-documented method of inducing lasting neuroplastic changes to the sensory pathways through repeatedly delivering a brief VNS burst paired with a sensory stimulus. Immediate effects occur upon VNS onset, often disappear upon VNS offset, and the modulation is present for all sensory stimuli. Conversely, the neuroplastic effects of pairing sub-second bursts of VNS with a sensory stimulus alters sensory processing only after multiple pairing sessions, this alteration remains after cessation of pairing sessions, and the alteration selectively affects the response properties of neurons encoding the specific paired sensory stimulus. Here, we call attention to the immediate effects VNS has on sensory processing. This review discusses existing studies on this topic, provides an overview of the underlying neuromodulatory systems that likely play a role, and briefly explores the potential translational applications of using VNS to rapidly regulate sensory processing.